Sovereignty of the state and national security in political philosophy - Elena F. Moros (Sovremennye Issledovaniâ Socialʹnyh Problem)
Background. In the modern world, characterized by globalization and the rapid development of information technologies, issues of national security and state sovereignty become particularly relevant. These aspects are interconnected and require an integrated approach to ensure political independence, economic stability, and preservation of cultural uniqueness of states. Research through realism, liberalism, and constructivism approaches allows for a deeper understanding of the relationship between sovereignty and national security. These concepts enrich the analysis and enable consideration of the problem from various perspectives, taking into account the diversity of approaches to this topic.